Trust, control and risks in interorganizational relationships within supply chains - Marconatto, Diego Antonio Bittencourt; Estivalete, Vania; Pedrozo, Eugenio Avila (Revista de Administração da UFSM, 2015)
The research efforts involving supply chains have not been investigating systematically the existent interrelations between interorganizacional trust, control and risks. Hence, this work aims to answer the following research question: How do interorganizacional trust, controls and risks affect each other in the context of supply chains? We perform it by employing the Das and Teng’s (2001) research framework into one of the largest Brazilian supply chains. Eight key propositions emerged from fifteen interviews and documental investigation. Altogether, such propositions allow to observe that (a) the joint analysis of interorganizacional trust, controls and risk provides a higher level of understanding of such elements in comparison with their individual analysis; (b) the various relationships between interorganizacional trust, controls and risks are complex, so linear research approaches are not adequate to comprehend their reality. The managerial implications of this study are the analytic capacity offered by the research framework for defining the types and extension of controls to be negotiated and for systemizing the largest risks to the business.